2007
DOI: 10.1080/13813450701531235
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NADPH oxidase subunit p22phoxby NF-kB in human aortic smooth muscle cells

Abstract: Accumulating evidence demonstrates the involvement of oxidative stress in the pathophysiology of cardiovascular diseases. The molecular mechanisms accountable for the increased production of reactive oxygen species remain uncertain. Among others, NADPH oxidase is one of the most important sources of superoxide in vascular cells. Here we investigate the role of NF-kB in the regulation of p22(phox) subunit and NADPH oxidase activity, in human aortic smooth muscle cells. Overexpression of p65/RelA or IKKbeta up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 39 publications
10
58
0
Order By: Relevance
“…Similar finding were reported in human monocytes/macrophages exposed to TNF (Gauss et al, 2007). Moreover, in previous studies we have shown that, NF-kB is an important transcriptional regulator of the genes coding for p22phox, Nox1, and Nox4, and has a profound impact in the up-regulation of Nox activity in TNF -treated human aortic SMCs (Manea et al, 2007;Manea et al, 2010b). The molecular mechanisms that facilitate hypoxia sensing and related signalling events are critical for the maintenance of vascular cell homeostasis.…”
Section: Phosphorylation Pathways and Transcription Factorssupporting
confidence: 71%
“…Similar finding were reported in human monocytes/macrophages exposed to TNF (Gauss et al, 2007). Moreover, in previous studies we have shown that, NF-kB is an important transcriptional regulator of the genes coding for p22phox, Nox1, and Nox4, and has a profound impact in the up-regulation of Nox activity in TNF -treated human aortic SMCs (Manea et al, 2007;Manea et al, 2010b). The molecular mechanisms that facilitate hypoxia sensing and related signalling events are critical for the maintenance of vascular cell homeostasis.…”
Section: Phosphorylation Pathways and Transcription Factorssupporting
confidence: 71%
“…Nox4 and p22 phox gene expression is regulated by the transcription factor nuclear factor-kappa B (NFjB) (26,28). We quantified levels of the inhibitory protein IjB as an indicator of the NFjB activity in PPHN lungs, and found that IjB protein levels were 52% lower in lung extracts from PPHN lambs relative to control lambs (Fig.…”
mentioning
confidence: 99%
“…More recent studies suggest that NF-kB upregulates Nox oxidase expression and production of Nox-dependent reactive oxygen species. Here, overexpression of p65/RelA or IKK up-regulated Nox1, Nox4, and p22phox, mRNA, and protein expression through direct binding of the respective promoters (Manea, et al 2007(Manea, et al , 2010. In contrast, NADPHdependent superoxide production (Nox activity) was reduced in the presence of NF-kB inhibitors.…”
Section: Redox Regulation Of Nuclear Factor Kappa B (Nf-kb) Signalingmentioning
confidence: 96%